Primary progressive multiple sclerosis presenting with severe predominant cognitive impairment and psychiatric symptoms: A challenging case. (October 2017) - Zambon, Alberto Andrea; Cecchetti, Giordano; Caso, Francesca; Santangelo, Roberto; Baldoli, Cristina; Natali Sora, Maria Grazia; Comi, Giancarlo; Magnani, Giuseppe; Martinelli, Vittorio
Severe cognitive dysfunction is a frequent feature of multiple sclerosis (MS), normally associated with later stages of the disease in adult population. Nevertheless, progressive cognitive and neuropsychiatric disturbances might rarely be the presenting and predominant symptom. In order to better characterize this peculiar phenotype of MS, we report on the case of a 38-year-old man who referred to our hospital with the suspect of hereditary leukodystrophy after 5 years of behavioral and mood abnormalities, global cognitive dysfunction, clumsiness, and very mild pyramidal and cerebellar signs. Brain and spinal magnetic resonance imaging (MRI) combined with cerebrospinal fluid (CSF) analysis prompted the diagnosis of MS.